Case study: auditory brain responses in a minimally verbal child with autism and cerebral palsy - Yau, Shu H.; McArthur, Genevieve; Badcock, Nicholas A.; Brock, Jon (Frontiers in Neuroscience, 2015)
An estimated 30% of individuals with autism spectrum disorders (ASD) remain minimally verbal into late childhood, but research on cognition and brain function in ASD focuses almost exclusively on those with good or only moderately impaired language. Here we present a case study investigating auditory processing of GM, a nonverbal child with ASD and cerebral palsy. At the age of 8 years, GM was tested using magnetoencephalography (MEG) whilst passively listening to speech and nonspeech sounds. Where typically developing children and verbal autistic children all demonstrated similar brain responses to speech and nonspeech sounds, GM produced much stronger responses to nonspeech than speech, particularly in the 65 – 165 ms (M50/M100) time window post stimulus onset. GM was retested aged 10 years using electroencephalography (EEG). Consistent with her MEG results, she showed an unusually early and strong response to pure tone stimuli. These results demonstrate both the potential and the feasibility of using MEG and EEG in the study of minimally verbal children with ASD.